Outpatient talc administration via indwelling pleural catheters for malignant effusions. Issue 4 (July 2019) - Dipper, Alexandra; Bhatnagar, Rahul; Maskell, Nick
Abstract : Purpose of review: Malignant pleural effusion is a common cause of breathlessness and signifies advanced disease. Common options for definitive pleural intervention include insertion of an indwelling pleural catheter (IPC) or talc pleurodesis. Recent findings: Administration of graded talc through an IPC offers an increased chance of pleurodesis compared with IPC drainage alone and is not associated with a significant risk of adverse events. Summary: In patients where an ambulatory treatment pathway is preferred, the increased chance of pleurodesis with talc administration via IPC can result in a faster time to device removal and may be associated with better quality of life and symptom scores.